Amiodarone Versus Lidocaine for Pediatric Cardiac Arrest Due to Ventricular Arrhythmias: A Systematic Review. Issue 2 (February 2017) - McBride, Mary E.; Marino, Bradley S.; Webster, Gregory; Lopez-Herce, Jesús; Ziegler, Carolyn P.; De Caen, Allan R.; Atkins, Dianne L.
Abstract : Objective: We performed a systematic review as part of the International Liaison Committee on Resuscitation process to create a consensus on science statement regarding amiodarone or lidocaine during pediatric cardiac arrest for the 2015 International Liaison Committee on Resuscitation's Consensus on Science and Treatment Recommendations. Data Sources: Studies were identified from comprehensive searches in PubMed, Embase, and the Cochrane Library. Study Selection: Studies eligible for inclusion were randomized controlled and observational studies on the relative clinical effect of amiodarone or lidocaine in cardiac arrest. Data Extraction: Studies addressing the clinical effect of amiodarone versus lidocaine were extracted and reviewed for inclusion and exclusion criteria by the reviewers. Studies were rigorously analyzed thereafter. Data Synthesis: We identified three articles addressing lidocaine versus amiodarone in cardiac arrest: 1) a prospective study assessing lidocaine versus amiodarone for refractory ventricular fibrillation in out-of-hospital adults; 2) an observational retrospective cohort study of inpatient pediatric patients with ventricular fibrillation or pulseless ventricular tachycardia who received lidocaine, amiodarone, neither or both; and 3) a prospective study of ventricular tachycardia with a pulse in adults. The first study showed a statistically significant improvement in survival to hospital admission with amiodarone (22.8% vs 12.0%; p = 0.009) and a lack of statistical difference for survival at discharge ( p = 0.34). The second article demonstrated 44% return of spontaneous circulation for amiodarone and 64% for lidocaine (odds ratio, 2.02; 1.36–3.03) with no statistical difference for survival at hospital discharge. The third article demonstrated 48.3% arrhythmia termination for amiodarone versus 10.3% for lidocaine ( p < 0.05). All were classified as lower quality studies without preference for one agent. Conclusions: The confidence in effect estimates is so low that International Liaison Committee on Resuscitation felt that a recommendation to use of amiodarone over lidocaine is too speculative; we suggest that amiodarone or lidocaine can be used in the setting of pulseless ventricular tachycardia/ventricular fibrillation in infants and children.